Impact of Tangible Resources and Human Resources AI Driven Capabilities on Innovative Behavior: Exploring the Moderating Role of Digital Leadership among Supply Chain Professionals - Bibi, Munaza; Usman, Muhammad Haider; Malik , Kaenat; Rizvi , Syed Muhammad Ahsan (Al-Qanṭara, 2025)
The Inclusion of artificial intelligence (AI) brings numerous changes in the management of organizational operations as well as employee outcomes. Subsequently, it influences the innovative behavior (IB) of professionals working in the supply chain (SC). Hence, in the recent organizational setting, digital leadership plays a crucial role in implementing AI capabilities and IB. However, limited studies exist that examine AI-driven capabilities linked to IB among supply chain professionals working in the Pakistani organizational setup from the lens of resource-based theory (RBT). Hence, this study examines the link between AI-driven capabilities including tangible and human resources and IB with the moderating role of digital leadership (DL). In order to conduct this study, a quantitative (deductive) approach was adopted. In addition, data were gathered from 452 supply chain professionals (SCP) working at different levels in the service sector of Pakistan. In addition, for data gathering, a survey design was executed. In order to implement the survey design around 600 questionnaires were disseminated. Of 600 disseminated questionnaires, only 472 were received in completed form. After assessment, only 452 were found fit for analysis using Smart PLS 4.0 to assess the validity and reliability as well as the relationship among variables. The analysis showed that increased tangible resources and human resources driven AI capabilities amplify the IB of supply chain professionals. Moreover, DL moderates the link between tangible resources and human resources driven AI capabilities and IB of supply chain professionals. This study examines the two critical resources that drive AI capabilities including tangible resources and human resources. This study will help practitioners develop strategies to build and train supply chain professionals for the execution of AI-related capabilities that can aid in spurring IB. Our study adds to the extant literature as little attention has been given to AI-driven capabilities that intricate resources from the lens of RBT. Moreover, no previous study has been conducted on assessing the AI-driven capabilities that affect IB by exploring the moderating role of DL among SC professionals.